2000
DOI: 10.1097/00001756-200004270-00003
|View full text |Cite
|
Sign up to set email alerts
|

Brain MRI lesions and atrophy are related to depression in multiple sclerosis

Abstract: It is unclear whether brain MRI lesions are associated with depression in multiple sclerosis (MS). Neurological dysfunction in depressed (n= 19) and non-depressed (n = 29) MS patients was rated by expanded disability status scale (EDSS). EDSS was weakly predictive of the presence of (p = 0.03) and severity of (p = 0.01) depression. After correcting for EDSS, the presence of depression was predicted by superior frontal and superior parietal hypointense TI lesions (p<0.01); the severity of depression was predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
3
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 218 publications
(138 citation statements)
references
References 2 publications
9
120
3
6
Order By: Relevance
“…Sullivan et al, 1995). The weight of most recent work favors an association between depression and demyelination, suggesting some disease-related contribution to depression in MS (Bakshi et al, 2000a;Berg et al, 2000;Fassbender et al, 1998;Feinstein, 2004;Pujol et al, 1997Pujol et al, , 2000Reischies et al, 1988;Zorzon et al, 2001). Certain brain regions may contribute disproportionately, as at least five published studies have reported greater temporal region involvement in depressed compared with nondepressed MS patients (Berg et al, 2000;Feinstein et al, 2004;Honer et al, 1987;Pujol et al, 1997;Zorzon et al, 2001).…”
Section: Pa Arnett Et Almentioning
confidence: 99%
“…Sullivan et al, 1995). The weight of most recent work favors an association between depression and demyelination, suggesting some disease-related contribution to depression in MS (Bakshi et al, 2000a;Berg et al, 2000;Fassbender et al, 1998;Feinstein, 2004;Pujol et al, 1997Pujol et al, , 2000Reischies et al, 1988;Zorzon et al, 2001). Certain brain regions may contribute disproportionately, as at least five published studies have reported greater temporal region involvement in depressed compared with nondepressed MS patients (Berg et al, 2000;Feinstein et al, 2004;Honer et al, 1987;Pujol et al, 1997;Zorzon et al, 2001).…”
Section: Pa Arnett Et Almentioning
confidence: 99%
“…While some comparative studies using MRI have found no differences in lesion distribution between depressed and non-depressed MS patients [38], other studies have suggested an increase in lesions in specific brain areas among depressed MS patients, including the right temporal lobe [41], the left hemisphere suprasylvian region [42], and the superior frontal or parietal regions. [43] Similarly, little is known about the specific nature of the interactions between the neuroimmunology of MS and depressive disorders. Hypothalamic feedback regulation is abnormal in many MS patients with 50% of MS patients demonstrating a failure of suppression on the dexamethasone suppression test.…”
Section: Neurobiology Of Depression In Msmentioning
confidence: 99%
“…Bakshi et al used MRI to study the relationship between lesion location, brain atrophy, and depression in patients with MS [53]. The presence of depression was related to T1 lesions in the superior frontal and superior parietal regions.…”
Section: Brain Lesions and Moodmentioning
confidence: 99%